A method for implementing a ship navigation simulator for the generation and utilization of virtual data - Min-Chul Kong; Myung-Il Roh (International Journal of Naval Architecture and Ocean Engineering, 2024)
Active research is underway to utilize various sensors for situational awareness, but validating these studies requires real sensor data, which is challenging to acquire due to the time and space constraints inherent in ships. Additionally, the diverse formats of sensor data and the need for postprocessing pose further hurdles. By developing a ship navigation simulator that faithfully replicates real-world environments, these limitations can be overcome, and ample virtual sensor data can be generated through immersive simulations. In this study, we propose a method for implementing such a simulator. A life-sized terrain model was placed within a virtual reality environment, representing maritime environments, including port structures. To simulate ship motions according to maritime weather conditions, we applied various laws of physics within virtual reality. Finally, to provide validation data for critical navigation technologies, such as collision avoidance and ship detection, we generated a virtual automatic identification system and camera data. We implemented and operated a ship navigation simulator using this approach, and simulations conducted across various environments generated real-time sensor data efficiently, affirming the effectiveness of the proposed method.